Obstetric red cell transfusion in a high-volume tertiary hospital: a retrospective cohort study - Eileen Lew; Karuna Mary Lional; Shephali Tagore (Singapore Medical Journal)
Introduction: Red cell transfusion is expensive and not without risks. Despite the availability of transfusion guidelines, studies report a wide interhospital variation in transfusion rates. This retrospective cohort study was conducted to define the incidence of red cell transfusion in a multi-ethnic obstetric population and to evaluate current transfusion practice with regard to indications and appropriateness. Methods: All parturients who delivered a live or stillbirth in the period 2014–2015 and who received allogeneic blood transfusion during pregnancy and up to six weeks postnatally were identified. Their medical records were reviewed to extract the relevant demographic, obstetric and transfusion data. Descriptive analysis of data was performed using IBM SPSS Statistics software. Results: Out of 23,456 parturients who delivered in the study period, 760 were administered red cell transfusion, resulting in a transfusion rate of 3.2% or 32 in 1,000 maternities. A total of 1,675 red cell units were utilised in 863 transfusion episodes. Major indications for transfusion were anaemia in pregnancy (49.2%) and postpartum haemorrhage secondary to an atonic uterus. Transfusion was more frequently associated with caesarean than vaginal births (4.9% vs. 2.4%). About 14% of transfusions were initiated with pre-transfusion haemoglobin (Hb) ≥8.0 g/dL, whereas 37% of transfusions resulted in post-transfusion Hb >9.0 g/dL. Conclusion: The incidence of red cell transfusion was 3.2% in a multiethnic obstetric population. Patient blood management strategies should focus on optimising antenatal anaemia, reducing blood loss during delivery and eliminating inappropriate transfusion.